2018
DOI: 10.3389/fpsyg.2018.00312
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Italian Version of the Young Schema Questionnaire L-3: Preliminary Results

Abstract: Schema Therapy (ST) is a well-known approach for the treatment of personality disorders. This therapy integrates different theories and techniques into an original and systematic treatment model. The Young Schema Questionnaire L-3 (YSQ-L3) is a self-report instrument, based on the ST model, designed to assess 18 Early Maladaptive Schemas (EMSs). During the last decade, it has been translated and validated in different countries and languages. This study aims to establish the psychometric properties of the Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 58 publications
(69 reference statements)
0
23
1
Order By: Relevance
“…All of the participants were administered the Italian version of the Yale Food Addiction Scale (YFAS) [ 34 ], the Young Schema Questionnaire Long Form, Third Edition (YSQ-L3) [ 35 ], the Binge Eating Scale (BES) [ 36 ], and the Hospital Anxiety and Depression Scale (HADS) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…All of the participants were administered the Italian version of the Yale Food Addiction Scale (YFAS) [ 34 ], the Young Schema Questionnaire Long Form, Third Edition (YSQ-L3) [ 35 ], the Binge Eating Scale (BES) [ 36 ], and the Hospital Anxiety and Depression Scale (HADS) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total scores are then averaged to indicate the level of each of the individual's schemas, with an average score of four or more suggested to be clinically meaningful (Lavergne, Marie, & Mehran, 2015;Young & Brown, 2003). Saggino et al (2018) reported high internal consistency for the 18 EMS in the YSQ-L3 in both their clinical (α ranged between .80 and .92) and non-clinical samples (α ranged between .83 and .94).…”
Section: Young Schema Questionnairementioning
confidence: 95%
“…Aside from the aforementioned studies, there is limited available literature on the factor structure of any of the long forms, including the English version of the YSQ-L3. The only other study on the YSQ-L3 was undertaken on the Italian version by Saggino et al (2018) using a large non-clinical (N = 918) and small clinical sample (N = 148). The absence of such investigations also highlights the lack of a clear methodological and statistical process for deriving the most pertinent items for a given EMS to include in the short-form YSQ, of which most schema research is based.…”
Section: Young Schema Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Marco experienced Narcissistic PD, with obsessive-compulsive, avoidant and passive-aggressive traits as assessed with the SCID-II (First et al, 2003). Maladaptive schemas were assessed with the Young Schema Questionnaire (YSQ; Saggino et al, 2018), showing heightened schemas of abandonment, abusemistrust, submissiveness and unrelenting standards. He had problems in emotion regulation assessed via the Difficulties in Emotion Regulation Scale (DERS; Sighinolfi et al, 2010).…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%